Firing Rate Homeostasis in Visual Cortex of Freely Behaving Rodents - Keith B. Hengen; Mary E. Lambo; Stephen D. Van Hooser; Donald B. Katz; Gina G. Turrigiano (2013)
Highlights•Cortical neurons in vivo return to a homeostatic firing rate set point when perturbed•Firing rate homeostasis is expressed in a cell-type-specific manner•Homeostatic firing rate set points are expressed across sleep and wake states•Firing rate homeostasis is correlated with the induction of synaptic scalingSummaryIt has been postulated that homeostatic mechanisms maintain stable circuit function by keeping neuronal firing within a set point range, but such firing rate homeostasis has never been demonstrated in vivo. Here we use chronic multielectrode recordings to monitor firing rates in visual cortex of freely behaving rats during chronic monocular visual deprivation (MD). Firing rates in V1 were suppressed over the first 2 day of MD but then rebounded to baseline over the next 2–3 days despite continued MD. This drop and rebound in firing was accompanied by bidirectional changes in mEPSC amplitude measured ex vivo. The rebound in firing was independent of sleep-wake state but was cell type specific, as putative FS and regular spiking neurons responded to MD with different time courses. These data establish that homeostatic mechanisms within the intact CNS act to stabilize neuronal firing rates in the face of sustained sensory perturbations.